PRODUCTION OF BIOLUBRICANT BLEND FROM JATROPHA CURCAS OIL (FUDMA JOURNAL OF SCIENCES, 2024)
Biolubricants derived from vegetable oils are environmentally compatible products due to their low toxicity and good biodegradability. Synthetic esters based on polyols and fatty acids possess suitable properties for lubricant applications, even at extreme temperatures. The current work investigates the oligomerization of fatty acid esters into biolubricant. The jatropha oil was esterified using recinoloeic acid and isobutyric acid over activated carbon from kaolin as a catalyst to produce biolubricant. Also, the carbon was prepared from kaolin through impregnation and activated with copper nitrate solution. The generated activated carbon was characterized using FTIR and XRF. The biolubricant (triesters) were produced via oligomeric fatty acid esters with recinoloeic acid under reflux at different reaction conditions and characterized using FTIR and GC-MS. Optimization of process parameters for oligomerization of jatropha oil with response surface based on Box-Beinkhen design. The process variables gave 90 min, 60oC and 1%, values corresponding to reaction time, reaction temperature and catalyst concentration as the optimal condition. A validation experiment was conducted to compare the optimal predicted value (93.07%) and experimental validated value (81.19%). The physicochemical properties of the jatropha oil and biolubricant produced were analyzed using ASTM methods. The quality parameters like kinematic viscosity, pour point, flash point viscosity index and blends of oil with that of commercial mineral oil were all in conformity with ASTM standard for biolubricant. The formulated oils also show the ability to significantly improve the kinematic viscosity, cold flow properties and possible potential as the replacement for the mineral-based lubricating oil
Keywords: Biolubricants; Synthetic esters; jatropha oil